Role of nasal irrigation by using alkaline nasal solution in allergic rhinitis treatment as an adjunct therapy - Periasamy, Chenthilnathan (2012)
Nasal irrigation is an important component in the management of upper respiratory tract diseases. Alkaline nasal solution plays vital role as an adjunctive therapy in the treatment of allergic rhinitis. Unfortunately, there still exits lack of evidence and practice regarding usage of alkaline solution as nasal irrigation in allergic rhinitis treatment. The aim of this study was to determine the effectiveness and role of nasal irrigation by using alkaline solution with any changes in nasal or non-nasal symptoms in the treatment of allergic rhinitis as an adjunct therapy. Besides, this study also analyzed for any side effects of alkaline nasal solution following its usage for the treatment of allergic rhinitis. This was a prospective, randomized control trial in which a total of 64 patients recruited fromHUSM and divided into Test group (n=32) and Control group (n=32). These patients confirmed suffering from allergic rhinitis with the presence of positive skin prick test. Then these patients of both groups, their symptoms will be assessed with a standardized and validated symptom score questionnaire pre and post study. Their symptoms were evaluated based on nasal and non - nasal symptoms. The test group had been given alkaline nasal solution as nasal irrigation for the period of 6 weeks along with regular nasal spray and antihistamine. Furthermore, the control group was given only the nasal spray and antihistamine for 6 week duration. During this study period, assessments of any adverse effect by usage of alkaline nasal solution as nasal irrigation in the Test group subjects were also analyzed. This study shows most of the sample subjects were middle age (21-40 years) and active earning group in which their daily routine and quality of life are strongly related to their allergic rhinitis symptom control. Most of the subjects were grouped into moderate/severe persistent allergic rhinitis. Furthermore majority of subjects in this study were allergic to house dust mite. This study shows statistically significant nasal symptom improvement in nasal discharge, nasal itchiness and sneezing among the Test group. There were no side effects noted in the usage of alkaline nasal solution during the study. Therefore alkaline nasal solution as nasal irrigation in the treatment of allergic rhinitis is beneficial. Nasal irrigation is a simple mode of treatment that relieves the symptoms with no documented adverse effects. Alkaline nasal solution as nasal irrigation has better effect on patient’s nasal symptoms and improves quality of life. Nasal irrigation techniques are simple and easily taught in primary health care. Moreover alkaline nasal solution is an important component in the management of allergic rhinitis as an adjunct therapy.